EDUCATION, TECHNOLOGY IN THE TEACHING OF SOCIAL SCIENCES (Journal of Universal Science Research, 2023)
This article explores diverse multidisciplinary research areas within the fields of education, technology, and social sciences. This article provides an overview of selected research areas and their intersections, highlighting their significance and potential for collaboration among disciplines. Drawing on relevant sources and references, this article aims to inspire researchers and scholars to explore innovative approaches and address complex challenges through multidisciplinary research.